2005
DOI: 10.1159/000084172
|View full text |Cite
|
Sign up to set email alerts
|

Erythrocyte Plasma Membrane Perturbations in Rats Fed a Cholesterol-Rich Diet: Effect of Drinking Sulphurous Mineral Water

Abstract: Aims: The purpose of the present study was to evaluate the ability of calcic and magnesic-sulphate-sulphurous spring mineral water (SMW) to reduce total and erythrocyte plasma membrane cholesterol in rats fed a cholesterol-rich diet. Methods: By using different fluorescent probes, 1,6-diphenyl-1,3,5-hexatriene (DPH), 1-[4-(trimethylamino)phenyl]-6-phenylhexa-1,3,5-triene (TMA-DPH) and Laurdan, a possible correlation was evaluated between cholesterol content changes of the membranes and membrane fluidity. Resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 62 publications
0
3
1
Order By: Relevance
“…The possible effects of demineralized water on kidney tissue need to be explored in further research. In contrast to research that states that the HDL and LDL levels are affected by the consumption of mineral-rich water (Nasuti et al, 2005). and that, depending on the duration of consumption, the total cholesterol and LDL cholesterol levels decrease while HDL levels increase (Granados et al, 2010), this research found that the consumption of either fresh, bottled, deionized and deionized water does not affect the blood total cholesterol, HDL and LDL cholesterols.…”
Section: Discussioncontrasting
confidence: 99%
“…The possible effects of demineralized water on kidney tissue need to be explored in further research. In contrast to research that states that the HDL and LDL levels are affected by the consumption of mineral-rich water (Nasuti et al, 2005). and that, depending on the duration of consumption, the total cholesterol and LDL cholesterol levels decrease while HDL levels increase (Granados et al, 2010), this research found that the consumption of either fresh, bottled, deionized and deionized water does not affect the blood total cholesterol, HDL and LDL cholesterols.…”
Section: Discussioncontrasting
confidence: 99%
“…Some authors underlined the importance of hydropinic treatment with calcic and magnesic-sulphate-sulphurous spring mineral water from the biomedical point of view, because it could represent an alternative approach in the interventions aimed at ameliorating biological injury deriving from hypercholesterolaemia. To evaluate the ability to reduce total and erythrocyte plasma membrane cholesterol by using calcic and magnesic-sulphate-sulphurous spring mineral water, a few studies have been performed on rats fed with a cholesterol-rich diet (Nasuti et al, 2005). In these studies, the rate of haemolysis was reduced in those erythrocyte suspensions in which cholesterol was increased, even if the enzymatic activity of glutathione peroxidase and catalase decreased.…”
Section: Biochemical Effects Of Mineral Watersmentioning
confidence: 99%
“…Of note, investigations of mineral waters in animal models presented conflicting [8,9]. A first study reported that, in fasting state, the consumption of Calcium/magnesium rich waters decreased plasma total cholesterol and LDL cholesterol in rat [9] while another study showed an increase in HDL cholesterol and stabilization of LDL cholesterol in rat fed cholesterol rich diet, with an active conversion of cholesterol into bile acid [10]. Investigations in human also reported some positive effects of mineral water consumption.…”
Section: Introductionmentioning
confidence: 99%